BPRS Performance Evaluation Using Importance-Performance Analysis (IPA) - Hidayat, Yayat Rahmat; Ibrahim, Mohammad Andri; Srisusilawati, Popon; Eprianti, Nanik; Wijayanti, Intan manggala (Univeristas Islam Bandung, 2023)
BPRS (Bank Pembiayaan Rakyat Syariah) is a bank that conducts its business activities based on Sharia procedures. However, its assets and financing are still relatively small compared to commercial banks. One of the reasons for this is that BPRS is limited in providing services for payment transactions. Therefore, it is important to evaluate the performance and customer satisfaction levels of BPRS. This study aims to measure the efficiency of BPRS performance using the Importance Performance Analysis (IPA) method. The research was conducted at PT. BPRS Bhakti Sumekar, a BPRS owned by the Regency Government of Sumenep. The results of this measurement can be used to evaluate the performance of BPRS Bhakti Sumekar in facing challenges and opportunities as well as for policy making considering its huge impact on the community. The results showed an average Conformity Level (TKi) of 99.57%, indicating that the performance of each attribute has met customer expectations but still requires improvement. The Customer Satisfaction Index (CSI) value resulting from this study was 75.45%, indicating that customer satisfaction with BPRS Bhakti Sumekar as a whole can be considered as satisfied. This customer satisfaction is based on the CSI interpretation table, which shows that the value obtained in this study falls in the range of 66% - 80.99%. This suggests that the performance of BPRS Bhakti Sumekar has almost reached customer expectations, leading to a high level of customer satisfaction.